First principles investigation of intrinsic and Na defects in XTe (X=Ca, Sr, Ba) nanostructured PbTe. (July 2021) - Zhang, Xuemei; Toriyama, Michael Y.; Male, James P.; Feng, Zhenzhen; Guo, Shuping; Jia, Tiantian; Ti, Zhuoyang; Snyder, G. Jeffrey; Zhang, Yongsheng
Abstract: Embedding isoelectronic and isostructural XTe (X = Ca, Sr, Ba) compounds in Na-doped PbTe can significantly boost thermoelectric performance through interface engineering and phonon scattering. Thus, defects in PbTe-based compounds play an essential role in improving the thermoelectric properties. In this study, we investigate the formation energies of charged intrinsic and extrinsic (Na) defects in a PbTe/PbXTe/XTe pseudo-interface. We find that different synthesis conditions of PbTe uniquely determine the lowest-energy defects. The low formation energies of Na Sr 1 − (and Na Pb 1 − ) play an important role in increasing the Na concentration in the solid solution PbTe/SrTe interface, in good agreement with the experimental observations. A low energy Na charged defect (n-type Na Te 3 + ) has been distinctly identified in the PbXTe solid solutions as well. Thus, the defect should be eliminated in the SrTe precipitated PbTe system for the p-type purpose. However, if experiments could synthesize the Pb0.5 Sr0.5 Te solid solution ingot, Na Te 3 + will play an important role to achieve the n-type behavior. While low energy defects have little effect on the electronic structures in PbTe and XTe, they enhance the density of states around the Fermi level in PbXTe solid solutions. Our work therefore not only elucidates the lowest energy defects in PbTe-based materials, but it also paves the way to understanding and designing promising thermoelectrics with interface phases. Graphical abstract: Image 1 Highlights: Understanding the defects behaviors in XTe (X = Ca, Sr, Ba) embedded PbTe compounds and the effects on thermoelectrics. The low Na 1- Sr/Pb defect formation energy rising the Na concentration in the solid solution PbTe/XTe interface. Identifying distinct lowest Na charged defect (n-type Na 3+ Te ) in the PbXTe solid solutions. Investigating the effects of low energy defects on the electronic structures and thermoelectric properties. Paving the way to design high promising thermoelectrics in other materials.